RETRACTED: Chitosan-Coated Titanium Dioxide-Embedded Paclitaxel Nanoparticles Enhance Anti-Tumor Efficacy Against Osteosarcoma - Qu, Yang; Kang, Mingyang; Cheng, Xueliang; Zhao, Jianwu (Frontiers in Oncology, 2020)
Objective Titanium dioxide nanoparticles (TiO2) nanoparticles have been widely explored in the prevention of cancer risk. Due to the difficult solubility of TiO2 nanoparticles, it is essential to synthesize new surfactants to increase its bioavailability and anti-tumor activity and reduce its cytotoxicity. Furthermore, oxidative and inflammation are closely associated with the osteosarcoma risk. Chitosan has biocompatibility, antioxidant and anti-inflammatory properties. The effects of chitosan-coated TiO2-embedded paclitaxel nanoparticles on an osteosarcoma model were explored. Methods An osteosarcoma model was established and chitosan-coated TiO2-embedded paclitaxel nanoparticles were prepared using a freeze-drying strategy. The morphological characteristics of nanoparticles were observed using scanning electron microscopy (SEM). The physicochemical properties of nanoparticle were evaluated by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The cytotoxicity was tested by using human osteoblast cells hFob1.19 and osteosarcoma cells 143B. Osteosarcoma mice were treated with PBS buffer, paclitaxel, TiO2-embedded paclitaxel and chitosan-coated TiO2-embedded paclitaxel nanoparticles. The biomarkers of oxidative-inflammatory status, anti-tumor activities and survival rates of the model were measured. Results XRD analysis showed that the peaks of chitosan/TiO2 (anatase) were consistent with those of crystalline TiO2 and broad phase of chitosan. The FTIR spectrum indicated the relevant functional groups in TiO2. Chitosan-coated TiO2-embedded paclitaxel nanoparticles had good biocompatibility and improve antioxidant and anti-inflammatory properties in the osteosarcoma model. Chitosan-coated TiO2-embedded paclitaxel nanoparticles was less toxic to the cells hFob1.19 and more toxic to the cells 143B than TiO2-embedded paclitaxel nanoparticles. Chitosan-coated TiO2-embedded paclitaxel nanoparticles showed significant antitumor activity and increased the survival rate of the osteosarcoma model (P < 0.05). Conclusions Chitosan improved anti-tumor potential of TiO2-embedded paclitaxel nanoparticles in the prevention of osteosarcoma.